DESIGN AND DEVELOPMENT OF COFFEE SHOP PHOTOBOOK AS AN INTRODUCTION TO FRACTAL PHOTOGRAPHY IN BATAM CITY - Fedric Tan; Muhammad Ardiansyah (Universitas Internasional Batam, 2022)
Photobook is a media that used to share a photographic product with a very high documentation value. Photobook can present or be a media to express the message content of an information on the topic to be raised. In making photobook, it is useful to introduce fractal photo styles by means of coffee shops in Batam City. A coffee shop is often defined as a hangout place for young people and parents who exist this day. The purpose of this research actually is to introduce the fractal photo style so that it can be more recognized by people in the city of Batam. Researchers will design fractal photography by using the Multimedia Development Life Cycle (MDLC) method to assist in the research process. The application used by the author in making the research is adobe photoshop CC 2018 and the results of the photo shoot will be used with the Xiaomi Mi 9. The photos were taken at 7 coffee shops and resulted in a total of 20 photo shoots from the results obtained. The tools used in taking photos are triangle prism, teardrop prism and crystal prism. The results of the development of this photobook will show how to take photos with fractal photography from several coffee shops in Batam City.